PENGARUH SISTEM INFORMASI AKUNTANSI, GAYA KEPEMIMPINAN DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA PEGAWAI PENGGUNA ENTERPRISE RESOURCE PLANNING (ERP) - Ni Wayan Ayu Ningsih; Sang Ayu Putu Arie Indraswarawati; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2020)
Every company needs a good employee performance in order to realize the company's goals. Similarly, companies in the field of public service activities such as PT. PLN (Persero). The formulation of the problem in this study is whether accounting information systems, leadership styles, and internal control systems affect the performance of ERP system user employees at PT PLN (Persero) Bali Distribution Parent Unit? The population used is all employees of the Enterprise Resource Planning system numbering 45 people at PT. PLN (Persero) Bali Distribution Parent Unit. The method of determining sample uses saturation sampling technique. After testing the instrument and testing the classical assumptions, data analysis is then performed using multiple linear regression analysis, determination, t test, and F test. The results of the analysis show that the influence of accounting information systems on employee performance obtained a regression coefficient of 0.165, the calculated t value of 2.890 and the t-test significance value of 0.006 <0.05, so H1 is accepted. The influence of leadership style on employee performance obtained a regression coefficient of 0.187, a calculated t value of 2.120 and a significant value of the t test of 0.040 <0.05, so that H2 was accepted. The influence of the internal control system on employee performance obtained a regression coefficient of 0.170, the calculated t value of 4.718 and the significant value of the t test of 0.000 <0.05, so that H3 is accepted. It is recommended to companies to provide motivation to employees who are still unable to show good performance, by providing compensation for employees with good performance so that other employees are motivated to work better.